'The history of the Ouinkai' – the alumni association of the Tokyo higher normal school for women: a milestone in Japan's education for women. Issue 2 (4th March 2019) - Sasaki, Keiko
ABSTRACT: The book, The History of the Ouinkai, was published in 1940 as a commemorative project for the 60th anniversary of the Tokyo Higher Normal School for Women (THNSW). The purpose of this article is to illustrate the type of data collected in the surveys and their findings, to explore some of the activities of the association, and to discuss how the Ouinkai alumni association, in collaboration with THNSW, worked with female teachers nationwide. The paper traces some of the multi-norms and multi-roles for female teachers that THNSW promoted and their relation to norms thought to characterise 'ideal' Japanese women. The publication of The History of the Ouinkai was a milestone in Japanese women's education because it demonstrated the Ouinkai's successes in respect of Japanese educational policy for women as well as the leadership that the Ouinkai provided to female graduate teachers, whom it organised with skill.